Aerosol Vaccination with AERAS-402 Elicits Robust Cellular Immune Responses in the Lungs of Rhesus Macaques but Fails to Protect Against High-Dose Mycobacterium tuberculosis Challenge - Darrah, Patricia A. (2014)
Development of a vaccine against pulmonary tuberculosis (TB) may require immunization strategies that induce a high frequency of antigen-specific CD4 and CD8 T cells in the lung. The nonhuman primate (NHP) model is essential for testing such approaches because it has predictive value for how vaccines elicit responses in humans. Here, we used an aerosol (AE) vaccination strategy to administer AERAS-402, a replication-defective recombinant adenovirus (rAd) type 35 expressing Mycobacterium tuberculosis (M.tb) antigens Ag85A, Ag85B, and TB10.4, in bacille Calmette-Guerin (BCG)-primed or unprimed rhesus macaques. Immunization with BCG generated low purified protein derivative (PPD)-specific CD4 T cell responses in blood and bronchoalveolar lavage (BAL). In contrast, aerosolized AERAS-402 alone or following BCG induced potent and stable Ag85A/b-specific CD4 and CD8 effector T cells in BAL that largely produced IFN-γ, as well as TNF and IL-2. Such responses induced by BCG, AERAS-402, or both failed to confer overall protection following challenge with 275 CFU of M.tb Erdman, although vaccine-induced responses associated with reduced pathology were observed in some animals. Anamnestic T cell responses to Ag85A/b were not detected in blood of immunized animals after challenge. Overall, our data suggest that a high M.tb challenge dose may be a critical factor in limiting vaccine efficacy in this model. However, the ability of AE rAd immunization to generate potent cellular immunity in the lung by AE rAd immunization suggests that using different or more immunogens, alternative rAd serotypes with enhanced immunogenicity, and a physiological challenge dose may achieve protection against M.tb.